2017
DOI: 10.1021/acs.est.7b00858
|View full text |Cite
|
Sign up to set email alerts
|

Isotope Tracing of Long-Term Cadmium Fluxes in an Agricultural Soil

Abstract: Globally widespread phosphate fertilizer applications have resulted in long-term increases in the concentration of cadmium (Cd) in soils. The accumulation of this biotoxic, and bioaccumulative metal presents problems for the management of soil-plant-animal systems, because the magnitude and direction of removal fluxes (e.g., crop uptake, leaching) have been difficult to estimate. Here, Cd isotopic compositions (δCd) of archived fertilizer and soil samples from a 66 year-long agricultural field trial in Winchmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 61 publications
0
25
1
1
Order By: Relevance
“…Furthermore, Cd isotope data for numerous different mineral P fertilizers reveal that the great majority are characterized by d 114/110 Cd values of less than 0.20&. [33][34][35] Use of such fertilizers in the more distant past is thus unlikely to have caused the observed high d 114/110 Cd ¼ 0.24& for the 0-5 cm topsoil at Site A-2 ( Fig. 2 and Table 2).…”
Section: Distribution and Isotope Fractionation In The Soilsmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, Cd isotope data for numerous different mineral P fertilizers reveal that the great majority are characterized by d 114/110 Cd values of less than 0.20&. [33][34][35] Use of such fertilizers in the more distant past is thus unlikely to have caused the observed high d 114/110 Cd ¼ 0.24& for the 0-5 cm topsoil at Site A-2 ( Fig. 2 and Table 2).…”
Section: Distribution and Isotope Fractionation In The Soilsmentioning
confidence: 98%
“…Such studies have already shown, however, that coupled Cd concentration and isotope data can be used to trace the origin of isotopically distinct Cd inputs, such as mineral P fertilizers, into soils. [31][32][33][34][35] In addition, isotope data can provide constraints on the distinct cellular and molecular processes that are employed by plants for the uptake, internal transport and sequestration of Cd. In particular, recent publications demonstrated that wheat and barley display similar trends of Cd isotope fractionation 33 and these differ signicantly from the isotope systematics observed for Cdtolerant and accumulator cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies reported on the use of stable isotopes at natural abundance to determine the impact of past anthropogenic Cd inputs on the current Cd stocks in soils. Salmanzadeh et al (2017) showed that the Cd stock of arable soils can be dominated by past applications of mineral P fertilizers. This finding is based on distinct isotope ratios of old and new mineral P fertilizers, which governed the Cd isotope compositions in the soils of a long-term field trial in New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…En la agricultura, la principal fuente de este metal es la aplicación de fertilizantes que contienen fosfatos, estos hacen que el Cd se acumule en suelos agrícolas y por lo tanto aumente el riesgo de su transferencia a través de la cadena alimentaria (Roberts, 2014;Salmanzadeh et al, 2017). Hoy en día, se necesitan urgentemente técnicas factibles para remediar los suelos contaminados con Cd y con ello; garantizar la inocuidad de los alimentos y proteger la salud pública (Guo et al, 2018a).…”
Section: Introductionunclassified